2016
DOI: 10.1371/journal.pone.0167445
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Stimulate Proliferation and Migration in Triple Negative Breast Cancer Cells

Abstract: Emerging evidence suggests that the adenosine (Ado) receptors may play crucial roles in tumor progression. Here, we show that Ado increases proliferation and migration in a triple negative breast cancer model, the MDA-MB 231 cell line. The use of specific agonists and antagonists evidenced that these effects depend on the activation of the A2B receptor, which then triggers an intracellular response mediated by the adenylate cyclase/PKA/cAMP signaling pathway. Ado also increases the expression of NaV1.5 channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 32 publications
(34 reference statements)
2
42
0
Order By: Relevance
“…e adenosine pathway is one of the major inhibitory pathways operating in the TME [28]. Previous studies have indicated that large amounts of adenosine accumulated in the hypoxic TME contribute to suppressing the immune response and promoting tumor progression [29][30][31]. According toÖztürk et al [32], aqueous extracts from S. marianum can inhibit ADA in gastric cancerous tissues and may have an important role in the immune regulation of GC.…”
Section: Discussionmentioning
confidence: 99%
“…e adenosine pathway is one of the major inhibitory pathways operating in the TME [28]. Previous studies have indicated that large amounts of adenosine accumulated in the hypoxic TME contribute to suppressing the immune response and promoting tumor progression [29][30][31]. According toÖztürk et al [32], aqueous extracts from S. marianum can inhibit ADA in gastric cancerous tissues and may have an important role in the immune regulation of GC.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that A2BR activation can enhance tumor growth [84,85,[106][107][108] and that targeting A2BR at the genetic level can reverse this effect [84,106,108]. A2BR activation has also been shown to play a role in the migration and metastasis of tumor cells [19,[108][109][110][111], due to the ability of A2BR to induce the epithelialmesenchymal transition (EMT) through activation of the ERK1/2 pathway [112,113]. Interestingly, Giacomelli et al [113] demonstrated that the activation of cAMP (mediated through A2BR activation) inhibited the EMT and that effects were more pronounced in the presence of a PKA inhibitor.…”
Section: Expression Of Adenosine Receptors and Signaling Pathways In mentioning
confidence: 99%
“…In breast cancer, for instance, A2b receptor expression is associated with poor survival in the triple negative (TNBC) subset 51 . Using A2b selective agonist (BAY 60‐6583) and antagonist (GS‐6201), A2b activation was shown to stimulated in vitro proliferation and migration of MDA‐MB‐231 cells 52 . A2b stimulation also increased expression of Na V 1.5 channels, 52 and was also described to promote breast tumor growth and metastasis 53 …”
Section: A2b Receptor In Cancermentioning
confidence: 99%